Uji Aktivitas Antibakteri Ekstrak Daun Tempuyung (Sonchus arvensis L.) terhadap Pseudomonas aeruginosa dan Bacillus cereus - Amrina Rosada; Baiq Yulia Hasni Pratiwi; Lalu Busyairi Muhsin (Universitas Bumigora, 2026)
Pseudomonas aeruginosa and Bacillus cereus are two dangerous pathogenic bacteria that are often resistant to antibiotics. This study aims to determine the antibacterial activity of the ethanol extract of tempuyung leaves (Sonchus arvensis L.) against Pseudomonas aeruginosa and Bacillus cereus bacteria. The antibacterial activity test used the well-diffusion method at extract concentrations of 10%, 25%, 50%, and 75%, with ciprofloxacin as the positive control and 10% DMSO as the negative control. The results of the antibacterial test showed that the extract did not produce an inhibition zone at any concentration against either bacterium, whereas the positive control showed a strong inhibition zone. Thus, the ethanol extract of tempuyung leaves was ineffective against Pseudomonas aeruginosa and Bacillus cereus under the tested conditions, with inhibition zones not exceeding the strong category. Further research is recommended to identify the active compounds using GC-MS and to test them on other types of bacteria.